Acupuncture treatment of Satoyoshi syndrome: a case report of a rare disease - Gong, Yu; Zhang, Xudong; Hao, Xiaomin; Liu, Jipeng; Yue, Bingnan; Liu, Chuan; Xia, Tianqi; Yang, Yi; Tu, Longteng; Qiu, WeiJie; Liu, Yu; Liu, Qingguo (Frontiers in Endocrinology, 2025)
BackgroundSatoyoshi syndrome (also known as Komuragaeri disease ) is a rare disorder of unknown etiology, with progressive muscle spasms, whole-body hair loss, and diarrhea as its main symptoms, particularly progressive skeletal muscle spasms and pain. Because of the lack of a clear etiology and pathogenesis of Satoyoshi syndrome, Western medicine lacks established effective therapies, and the long-term prognosis of the treatment of this disease is poor, unable to improve multiple symptoms simultaneously and prevent the recurrence of the disease. In recent years, acupuncture has been increasingly explored as a complementary treatment for autoimmune diseases. It is believed to exert its effects by modulating the neuroendocrine-immune network, enhancing immune cell function, and restoring homeostatic pathways. These mechanisms enable acupuncture to provide immune modulation, ultimately achieving a holistic and bidirectional regulatory effect.Case descriptionWe report the case of a 54-year-old male police officer who had Satoyoshi syndrome for more than five years. After six months of acupuncture treatment, the patient’s chronic diarrhea completely disappeared, and the occasional painful muscle cramps and insomnia significantly improved. After six months of follow-up, the patient’s condition was stable.ConclusionIn this study, we believe that acupuncture therapy is of great significance for the improvement of diarrhea, immediate and long-term analgesia, and stabilization of the Satoyoshi syndrome.